POSTGIS-T: TOWARD A SPATIOTEMPORAL POSTGRESQL DATABASE EXTENSION - Simoes, Rolf Ezequiel de Oliveira; Queiroz, Gilberto Ribeiro de; Ferreira, Karine Reis; Vinhas, Lubia; Camara, Gilberto (Revista brasileira de cartografia, 2017)
The temporal dimension of spatial data has been the subject of discussion in the literature for a long time. While there are numerous Database Management System (DBMS) solutions for spatial dimension, we do not observe the same situation for spatiotemporal data. Considering this gap, our purpose is to design and implement an extension to PostgreSQL DBMS that is based on a formal spatiotemporal algebra in order to incorporate representations of spatiotemporal data within the DBMS. The proposed extension can be used in a large range of applications. We intend this extension to be a reasonable framework to store and handle observational remote sensing data usually present in applications like animal migration researches, wildï¬ res monitoring, vessel tracking for monitoring ï¬ shing, and other similar applications. In this work, we show how to apply it in a case study based on spatiotemporal data collected from drifting buoys belonging to the NOOA's Global Drifter Program.